Oxyresveratrol ameliorates nonalcoholic fatty liver disease by regulating hepatic lipogenesis and fatty acid oxidation through liver kinase B1 and AMP-activated protein kinase. (1st June 2018) - Lee, Ju-Hee; Baek, Su Youn; Jang, Eun Jeong; Ku, Sae Kwang; Kim, Kyu Min; Ki, Sung Hwan; Kim, Chang-Eop; Park, Kwang Il; Kim, Sang Chan; Kim, Young Woo
Abstract: Oxyresveratrol (OXY) is a naturally occurring polyhydroxylated stilbene that is abundant in mulberry wood ( Morus alba L.), which has frequently been supplied as a herbal medicine. It has been shown that OXY has regulatory effects on inflammation and oxidative stress, and may have potential in preventing or curing nonalcoholic fatty liver disease (NAFLD). This study examined the effects of OXY on in vitro model of NAFLD in hepatocyte by the liver X receptor α (LXRα)-mediated induction of lipogenic genes and in vivo model in mice along with its molecular mechanism. OXY inhibited the LXRα agonists-mediated sterol regulatory element binding protein-1c (SREBP-1c) induction and expression of the lipogenic genes and upregulated the mRNA of fatty acid β-oxidation-related genes in hepatocytes, which is more potent than genistein and daidzein. OXY also induced AMP-activated protein kinase (AMPK) activation in a time-dependent manner. Moreover, AMPK activation by the OXY treatment helped inhibit SREBP-1c using compound C as an AMPK antagonist. Oral administration of OXY decreased the Oil Red O stained-positive areas significantly, indicating lipid droplets and hepatic steatosis regions, as well as the serum parameters, such as fasting glucose, total cholesterol, and low density lipoprotein-cholesterol in high fat diet fed-mice, as similar with orally treatment of atorvastatin. Overall, this result suggests that OXY has the potency to inhibit hepatic lipogenesis through the AMPK/SREBP-1c pathway and can be used in the development of pharmaceuticals to prevent a fatty liver. Highlights: Oxyresveratrol inhibited liver X receptor α-mediated sterol regulatory element binding protein-1c. Oxyresveratrol regulated the genes of lipogenesis and β-oxidation. Oxyresveratrol activated of liver kinase B1 and AMP-activated protein kinase. Oral administration of oxyresveratrol decreased fatty liver in high fat diet fed-mice. Oxyresveratrol treated hepatic lipogenesis through the AMPK/SREBP-1c pathway.